Influence of Adding Goroho’s (Musa sp) Banana on nutrient content and Organoleptic Tuna Shredded (Katsuwonus pelamis) - Pakaya, Rini; Mandey, Lucia C.; Lumoindong, Frans (Jurnal Ilmu dan Teknologi Pangan, 2015)
This shredded protein nutritional value 28.18 %; fat 19.16 %; ash 3.45% and crude fiber 1.28%. Tuna shredded Processingwith the addition of goroho’sbanana expected gets sufficiency  animal protein and vegetable. This research aims to determine the influence of goroho’s banana through organoleptic test and analyze the nutrient content of shredded tuna are good quality in accordance with SNI. This research utilize a completely randomized design (CRD) with the object of research white meat tuna and goroho’s banana with  of mixing treatment between white meat tuna, goroho’s banana bud and condiments as garlic, red onion, handover, ginger and palm sugar .The results showedthat thesensory qualityof shreddedtunawiththe additionof goroho's banana bud most preferred use concentration of75% white meattunaand25% goroho's banana bud. Keywords : shredded,  goroho’s banana bud, tuna, proximate analysis and organoleptic